Studi Identifikasi Struktur Geologi Bawah Permukaan Untuk Mengetahui Sistem Sesar Berdasarkan Analisis First Horizontal Derivative (FHD), Second Vertical Derivative (SVD), Dan 2,5D Forward Modeling Di Daerah Manokwari Papua Barat - Ahmad Zaenudin; Shiska Yulistina (Engineering Faculty Universitas Lampung, 2018)
In general, Manokwari has a geological structure that is in the form of a folding area found in the highlands of the mountains. Among the creases, there is a fault up and the fault down. In coastal or marine areas found many reefs and corals. The study of gravity was conducted in the Manokwari area of West Papua with the aim to know the subsurface geological structures based on FHD (First Horizontal Derivative), SVD (Second Vertical Derivative) and 2.5D Forward Modeling on the residual anomaly maps of the study area. The results showed that the research area has Bouguer Anomaly value ranged from 4 mGal to 96 mGal with the low anomaly at the left side of the research area lengthwise relatively in north-west to south-east direction, the middle-value anomaly spreads in the west-east area of research area, high anomaly scattered in the northern part of the research area. The results of the 2.5D subsurface modeling and the SVD and FHD analysis indicated the presence of a Thrust Fault on the C-C’ cross-section, on the B-B’ cross-section there is a Diorite Lembai intrusion with the density value is 2.75 gr/cc, whereas the A-A' cross-section which intersects with Sorong fault were not found any fault or rock intrusion based on observed gravity data of the research area.